Ethics and humanity : themes from the philosophy of Jonathan Glover - Davis, N. Ann.; Keshen, Richard, 1946-; McMahan, Jeff. (New York ; Oxford : Oxford University Press, 2010)
This work pays tribute to Jonathan Glover, a pioneering figure whose thought and personal influence have had a significant impact on applied philosophy.The papers collected here address topics to which Glover has contributed.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Glover, Jonathan; Ethics -- History -- 20th century; Ethics, Modern -- 20th century; Humanity